From PP waste to high-quality products: Decontamination of the material throughout the entire recycling process chain using state-of-the-art technologies (2024)
Turning waste into high-quality products should be the aim of recycling, but it requires considerable effort to separate specific materials from others, clean them properly, and reconvert them into products. Such a process chain of mechanical recycling of post‑consumer polypropylene (PP) from a mixed waste collection was conducted with an advanced combination of state‑of‑the‑art technologies considering the material’s decontamination throughout the different process steps. The levels of solid and volatile contamination were analyzed with an optical control system and a gas chromatographic method, respectively, and were found to decrease in varying amounts throughout the process. The results of this study represent the currently achievable qualities of recycled PP in mechanical recycling and, based on these findings, the recycling process can be further improved.